Ghana Feed the Future Innovation Lab for Small-Scale Irrigation (ILSSI) Endline Survey, 2017 - International Food Policy Research Institute (International Food Policy Research Institute, 2024)
The Feed the Future Innovation Lab on Small-Scale Irrigation (FTF-ILSSI) is a cooperative agreement funded by USAID under the Feed the Future program to undertake research aimed to increase food production, improve nutrition, accelerate economic development and contribute to the protection of the environment. The project seeks these objectives through identifying, testing and demonstrating technological options in small-scale irrigation and irrigated fodder, supported by a continual dialogue approach with stakeholders and capacity development toward sustained use of research approaches and evidence. Collaborators on this project include Texas A&M University, the International Water Management Institute (IWMI), the International Food Policy Research Institute (IFPRI), the International Livestock Research Institute (ILRI), North Carolina A&T State University (NCAT) and Texas A&M AgriLife Research (TAMUS). As part of this project, IFPRI is undertaking a study of irrigating and non-irrigating households in Ethiopia, Tanzania and Ghana to investigate the connections between irrigation, gender, nutrition and health. The survey explores these linkages through an in-depth household questionnaire with questions on agricultural production, nutrition and health, a WEAI module and a community questionnaire. This work forms part of the CGIAR Research Program on Water, Land and Ecosystems (WLE).